Management of Thrombocytopenia with Partial Splenic Embolization in Liver Cirrhosis - Putri, Septia Harma; Arnelis; Saptino Miro (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Thrombocytopenia is a frequent complication in patients with cirrhosis. Thrombocytopenia is generally divided into mild, moderate, and severe thrombocytopenia. Thrombocytopenia in liver cirrhosis not only increases the risk of bleeding during surgery but can also have an impact on patient management, such as liver biopsy, administration of antiviral therapy, and postponement of elective surgery. The pathophysiology of thrombocytopenia in chronic liver disease can be caused by decreased platelet production, sequestration in the spleen, and increased platelet destruction. Partial splenic embolization (PSE) is one option for treating thrombocytopenia in chronic liver disease. PSE is an effective procedure in treating complications associated with hypersplenism and portal hypertension, such as esophageal varices, pancytopenia, portal hypertensive gastropathy and ascites.